Dua Sisi Auditing: Audit Eksternal dan Internal Pemerintah - Boby Segah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
In Indonesia, there are several Supervisory Institutions, such as the Supreme Audit Agency, the Financial and Development Supervisory Agency, the Inspectorate General and the Inspectorate in each Ministry, Institution, Provincial Region and District / City Region. Audited government institutions often question what are the differences and similarities between the oversight institutions. In addition, they do not yet know which external audit institutions and internal audit institutions are Government Agencies among these oversight institutions. Many people assume, including among government institutions that assume that every audit, whoever is implementing it is the same. What they know is that each inspector or auditor has the same activities. Everything borrows a lot of files, tests every document, checks physically, check cash/banks, asks a lot, and what they understand more is all auditors, who are tasked with finding findings and finding problems. From the problem identified above, the problem is formulated that there needs to be clarity about the similarities and differences between external and internal audits in government circles